STRATEGI PENYELESAIAN MASALAH PADA PERKULIAHAN ANATOMI TUMBUHAN UNTUK MENUMBUHKAN KETERAMPILAN BERFIKIR MELALUI IDE INOVATIF - Rinie Pratiwi Puspitawati (Jurnal Pendidikan Biologi, 2015)
This study aimed to describe the innovative ideas related to the concept of plant natomy and learning outcomes are achieved. This research was carried out by implementing a pattern of lecture-based problem solving. Through problem solving, students can develop the thinking process to find the problem and think about a solution, at the same time bring innovative ideas.  Indicators of thinking skills that can be used to mark the emergence and possible feasibility of innovative ideas include learning outcomes (1) formulating the proposed study plant anatomy relevant to the phenomenon that is chosen as the background of the results of the appreciation of the performance problem resolution and (2) the visibility of innovative ideas, including ( a) formulation of the problem, (b) the formulation of objectives, (c) the formulation of temporary answer, (d) the definition of the factors or variables that were examined, (e) definition of factors or variables are equal, (f) the definition of the factors or variables were observed, (g ) formulation of outcome indicators, and (h) working draft. The results obtained showed the longer experience of student learning through problem solving, the more students are able to formulate innovative ideas. There is a link between the learning outcomes concept of plant anatomy with the achievements of thinking skills are realized through innovative ideas formulated.Keywords: Problem Solving Strategies, Plant Anatomy, Innovative Idea